Haemangiomas of the orbit - Justová, Eva; Pazdera, Jindrich; Mihál, Vladimír; Nekula, Josef (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2003)
The authors describe their experience with systemic therapy of cavernous haemangiomas making use of interferon alpha. They have successfully used the method in treating two female patients with cavernous haemangiomas in the orbit. In the first patient, the IFN therapy was followed by surgical removal of the tumour. In the second patient, surgical operation was not suitable. After the IFN therapy, the patient's state improved both subjectively and objectively. Decreased level of bFGF in urine prove to be the criterion for successful treatment by IFN. The authors also stress the risk of complications in sucklings. When choosing the method of treatment, they emphasize the necessity of interdisciplinary cooperation.
Keywords: nádory orbity; lidé středního věku; Adult; Orbital Neoplasms; lidé; dospělí; Female; ženské pohlaví; Interferon-alpha; kavernózní hemangiom; Middle Aged; Humans; interferon alfa; Hemangioma, Cavernous